Interrelationship identification between humans from images using two class classifier - Verma, Amit; Meenpal, T; Acharya, B (International Journal of Engineering and Technology, 2018)
The paper proposes an automatic interrelationship identification algorithm between human beings. The image database contains two interrelationship classes i.e. two people hugging and handshaking each other. The feature detection and feature extraction has been done using bag of words algorithm. SURF features and FAST features are used as feature detectors. Finally, the extracted features have been applied to SVM for classification. We have tested the classifier against a set of test images for both feature detectors.Â Finally, the accuracy of the classifier has been calculated and confusion matrix has been plotted.Â Â